(untitled) (Scientific journal of the Fergana State University, 2024)
The article is devoted to the study of the influence of art pedagogy on the development of students’ creative outlook. Art pedagogy is an innovative direction, the goal of which is to create a new cognitive methodology, to eliminate psychological barriers to thinking, to reflect intellectually and creatively, to educate and creatively organize the interaction between teachers and students. is to build without. This technology is especially relevant in the ability to integrate art into the educational context to solve the professional and pedagogical tasks of modern educational practice. The purpose of the article is to study the impact of art pedagogy techniques on the development of creative thinking in students, and the opinions of scientists about art pedagogy, as well as personal-scientific advice and opinions on the development of students’ creative thoughts using these methods. A scientific article consists of theoretical analysis, generalization, survey and research of literature.